2017
DOI: 10.1128/aac.00363-17
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity and Resistance Analysis of NS3/4A Protease Inhibitor Grazoprevir and NS5A Inhibitor Elbasvir in Hepatitis C Virus GT4 Replicons

Abstract: Although genotype 4 (GT4)-infected patients represent a minor overall percentage of the global hepatitis C virus (HCV)-infected population, the high prevalence of the genotype in specific geographic regions coupled with substantial sequence diversity makes it an important genotype to study for antiviral drug discovery and development. We evaluated two direct-acting antiviral agents-grazoprevir, an HCV NS3/4A protease inhibitor, and elbasvir, an HCV NS5A inhibitor-in GT4 replicons prior to clinical studies in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
(49 reference statements)
1
23
0
Order By: Relevance
“…The present study indicates that the most prevalent subtypes of GT4 HCV, 4a and 4d, respond very well to LDV/SOF treatment, with 25 of 25 and 10 of 10 patients achieving SVR12 following 12 weeks of treatment (Table S1) GT4b (3.6-34 nmol/L) compared to other subtypes of GT4 (range: 0.0002-0.072 nmol/L for subtypes 4a/d/f/g/m/o/q) has also been reported. 24,25 Although the number of patients is small for some subtypes of GT4 in this study, the results are in agreement with the observation from Halfon et al 26 This suggests that specific triple and quadruple substitutions may affect LDV susceptibility differentially depending on the HCV GT4 subtype. This observation is supported by the difference in EC 50 values for patient isolates from different subtypes exhibiting the same NS5A…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study indicates that the most prevalent subtypes of GT4 HCV, 4a and 4d, respond very well to LDV/SOF treatment, with 25 of 25 and 10 of 10 patients achieving SVR12 following 12 weeks of treatment (Table S1) GT4b (3.6-34 nmol/L) compared to other subtypes of GT4 (range: 0.0002-0.072 nmol/L for subtypes 4a/d/f/g/m/o/q) has also been reported. 24,25 Although the number of patients is small for some subtypes of GT4 in this study, the results are in agreement with the observation from Halfon et al 26 This suggests that specific triple and quadruple substitutions may affect LDV susceptibility differentially depending on the HCV GT4 subtype. This observation is supported by the difference in EC 50 values for patient isolates from different subtypes exhibiting the same NS5A…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that the reported substitution combinations are the sole contributor to LDV in vitro resistance in the GT4b isolates. Interestingly, a significantly higher median EC 50 for elbasvir against GT4b (3.6‐34 nmol/L) compared to other subtypes of GT4 (range: 0.0002‐0.072 nmol/L for subtypes 4a/d/f/g/m/o/q) has also been reported …”
Section: Discussionmentioning
confidence: 86%
“…Elbasvir (EBV), an NS5A inhibitor and Grazoprevir (GZR), an NS3/4A protease inhibitor, have demonstrated high in vitro potency against HCV genotype 1 and 4 replicons, as well as resistance‐associated substitutions (RASs) that confer resistance to first‐generation protease inhibitors and RASs related to treatment failures on DCV and LDV …”
Section: Elbasvir/grazoprevir (Zepatier)mentioning
confidence: 99%
“…Cell culture studies demonstrated antiviral activity of each drug component against each approved GT, with data generally demonstrating consistent activity across several representative subtypes of GT 4 and 6. Although it is not feasible to capture all of the genetic diversity of GT 4 and 6 subtypes in cell culture studies and clinical trials, antiviral activity generally has been demonstrated, at minimum, across the most common representative subtypes of GT 4 and 6…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture studies demonstrated antiviral activity of each drug component against each approved GT, with data generally demonstrating consistent activity across several representative subtypes of GT 4 and 6. Although it is not feasible to capture all of the genetic diversity of GT 4 and 6 subtypes in cell culture studies and clinical trials, antiviral activity generally has been demonstrated, at minimum, across the most common representative subtypes of GT 4 and 6 [10][11][12][13][14][15][16][17][18][19][20][21] To describe characteristics of less common GTs and relevant subgroups represented in clinical trials, we conducted an analysis of DAA clinical trials evaluating FDA-approved regimens for treatment of HCV GT 4, 5 or 6 infection. Specifically, the objectives of our analyses were to describe the representation and geographic distribution of GT 4 and 6 viral subtypes in clinical trials and to summarize the treatment outcomes for GT 4, 5 and 6 with FDA-approved DAA regimens.…”
Section: Introductionmentioning
confidence: 99%